Guía didáctica de los Briófitos del Campus Salache, Universidad Técnica de Cotopaxi 2018-2019 - Segura Ortega, Daniela Alejandra (2019)
This Project is focused in reinforce the Universidad Técnica de Cotopaxi herbarium´s (UTCEC) with non-vascular plant group collections´s (Bryophyte) emphasizing the Salache campus. This Works contemplated a set of activities such as: delimitation of the study area in four zones (low, medium, high, mountainous) for facilitation of sampling and collection of specimens present in the about mention areas in all available substrates (soil, rock, on tree, leaf), assembly of samples, dissections, micro photographed and finally, identification of specimens by taxonomic keys. Among the results of this research we can mention the inventory of the brioflora of the Salache campus, consisting of 11 species distributed in a thalli liverworts (Marchantiaceae, Marchantia polymorpha) and 10 mosses: Barbula, Didymodon, Syntrichia, Pseudosymblepharis, Tortula, Pseudocrossidium (Pottiaceae), Bryum argentum (Bryaceae), Fabronia ciliaris (Fabroniaceae), Orthotrichum (Orthotrichaceae), Funaria hygrometrica (Funariaceae). The Pottiaceae was the family with the greatest diversity of species (6 species / 6 genera), which is a characteristic taxon of acid soils, open and anthropogenically intervened environments. All the information generated in this research, is condensed in a didactic guide of the bryophytes of the Salache campus, which put together the digital media the descriptions, geography location, photographs and taxonomic keys of the 11 species inventoried in this study, to facilitate students, teachers and general public understand this tiny group of plants. It is recommended to continue with similar studies in other areas of the Province, with standardized methodologies to better understand the composition and behavior of the bryophyte communities in Ecuador.